1982
DOI: 10.1136/gut.23.6.498
|View full text |Cite
|
Sign up to set email alerts
|

Features of small intestinal pathology (epithelial cell kinetics, intraepithelial lymphocytes, disaccharidases) in a primary Giardia muris infection.

Abstract: SUMMARY In an attempt to correlate host and parasite-related events occurring during the course of a primary Giardia infection in the mouse we have measured epithelial cell kinetics, enzymes, and intraepithelial lymphocytes at different stages of the infection. New methods were developed for the accurate measurement of parasite numbers and distribution within the gut. In jejunum a modest decrease in villus length and intraepithelial lymphocytes at week 1 preceded a pronounced disaccharidase deficiency at week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 18 publications
4
41
0
Order By: Relevance
“…While Giardia trophozoites preferentially colonize the most proximal small intestine ( Fig. 2A) (47)(48)(49), they are also found in the distal small intestine, as well as the cecum and large intestine (47)(48)(49). Within the antibiotic-treated proximal small intestine, we found that Giardia infection substantially changed the diversity of the host microbiota during the 14-day course of infection ( Fig.…”
Section: Figmentioning
confidence: 72%
“…While Giardia trophozoites preferentially colonize the most proximal small intestine ( Fig. 2A) (47)(48)(49), they are also found in the distal small intestine, as well as the cecum and large intestine (47)(48)(49). Within the antibiotic-treated proximal small intestine, we found that Giardia infection substantially changed the diversity of the host microbiota during the 14-day course of infection ( Fig.…”
Section: Figmentioning
confidence: 72%
“…Increased infiltration of intraepithelial lymphocytes has been associated with giardiasis in a number of reports (24,40,56). As the findings reported here implicate T lymphocytes in the brush border abnormalities caused by the disease, and as epithelial injury and malfunction were associated with reduced jejunal IL-6, additional experiments assessed whether these changes paralleled alterations in IEL infiltration in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that excess IL-6 is associated with decreased activity of sucrase-isomaltase (57), a brush border enzyme which is also markedly decreased in patients with active Crohn's disease or giardiasis. Hosts infected with Giardia commonly mount a humoral immune response, and there is no noticeable granulocytic cell influx into the intestine during the acute phase of giardiasis although the immune response to Giardia unquestionably involves activation of T lymphocytes (20,24,27,29,49,53,54). The antibody response to Giardia is predominantly of the IgA and IgG isotypes (4,27).…”
mentioning
confidence: 99%
“…First, in immuno-competent but not in T-cell deficient animals, acute giardiasis causes a diffuse loss of epithelial brush border surface area and decreases sucrase and maltase activities (Scott et al 2000). During the acute phase of the infection, epithelial abnormalities were not seen in the jejunum of Gupta et al 1973, Chawla 1975, Ducombe et al 1978, Gillon et al 1982, Faubert 1988, Belosevic et al 1989, 1992, Favennec et al 1991, Katelaris et al 1991, Cevallos et al 1995, Mohammed et al 1995, O'Handley et al 2001 athymic mice, despite comparable parasitic loads to those seen in immuno-competent animals, implying that the lack of microvillous injury could not be attributed to a reduction in trophozoite numbers. Second, experiments using in vivo T lymphocyte transfer into naïve animals demonstrate that brush border injury and malfunction in giardiasis are mediated by CD8 + T lymphocytes, while CD4 + T lymphocytes are responsible for parasite clearance (Scott et al 2004).…”
Section: The Role Of Cd8 + Lymphocytes In Pathogenesismentioning
confidence: 99%
“…Increased infiltration of intraepithelial lymphocytes (IEL) has been associated with giardiasis in a number of reports (Gillon et al 1982, Oberhuber et al 1996, Wakelin 1997. Intriguingly, this increase was reported in immunocompetent as well as in athymic animals infected with Giardia (Scott et al 2000), suggesting a role for extrathymic differentiation in this response.…”
Section: Lymphocytes In Giardiasis: Friends or Foes?mentioning
confidence: 99%